Sent - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2010)
Jonah, Katherine, Chip, and Alex suddenly find themselves in 1483 at the Tower of London, where they discover that Chip and Alex are Prince Edward V and Richard of Shrewsbury, imprisoned by their uncle, King Richard III, but trying to repair history without knowing what is supposed to happen proves challenging. Author's note includes historical facts about the princes and king.
Includes excerpt from author's next book in the same series, "Sabotaged" (p. [315]-[325]).
730L
Keywords: Edward -- 1470-1483; Richard, -- 1472-1483; Richard, -- 1452-1485; Space and time; Science fiction; Space and time; Great Britain -- History -- Richard III, 1483-1485